The Impact of Exports on Malaysian Economic Development: A Comparative Study between Japan and Germany - Furuoka, Fumitaka (AEI Insights, 2021)
This paper aims to conduct a comparative study and to examine whether Malaysia’s exports to its trade partner in Asia would be more beneficial than its counterpart in Europe. For this purpose, the current study examines Malaysia’s exports to Japan and Germany and their impacts on Malaysia’s economic development. The current study uses three types of econometric analysis, namely the unit root test, the co-integration test and the causality test. The empirical findings indicated three main points. Firstly, the ADF unit root test showed that income and exports are integrated of order one. In other words, these variables could be considered as stationary process at the first difference. Secondly, the EG test indicated that there would be no long-run relationship between income and exports from Malaysia to Japan. The co-integration test showed that there would be no long-run relationship between income and exports from Malaysia to Germany. Finally, the Granger causality test showed that there would be no causal relationship between income and exports from Malaysia to Japan. By contrast, the causality test indicated that there would be a causal relationship between exports from Malaysia to Germany and economic development in Malaysia.